Application of Decision Support System for Selection of Residential Criteria using the fuzzy Method in Majene Regency - Irianti, Arnita; Quraisy, Muh. Imam; Sulfayanti, Sulfayanti; Nur, Nahya; Ardi, Rahmawati (Politeknik Caltex Riau, 2024)
In this digital era, information technology is growing rapidly so that it is used to market various things, including homes. There is a lot of information technology about houses being marketed, but it takes a long time to collect information and compare one house to another. However, some of the housing marketed no longer prioritizes comfort, but rather cheap or economical prices. Due to the fact that sometimes unclear data is needed to solve problems, the fuzzy method is a decision-making approach that uses standard relationships but applies fuzzy set theory to the database. Decision making regarding the selection of comfortable housing criteria according to consumers is carried out using the fuzzy Tahani model approach. The fuzzy holdi technique uses house data that has been processed to produce output in the form of house data that is recommended for customers.